Ceramic manufacturing techniques and cultural traditions in Nubia from the 8th to the 3rd millennium BC : examples from Sai Island - D'Ercole, Giula (Cambridge monographs in African archaeology, 2017)
In Sudan the first ceramic containers appeared at the beginning of the 9th millennium BC, with the earliest dates c. 8700 BC from Sorourab 2, in Central Sudan, and c. 8600 BC from the district of Amara West, in Northern Sudan. This work presents a comprehensive critical analysis of diverse ceramic assemblages from Sai Island, in the Middle Nile Valley of Northern Sudan, on the border between ancient Upper and Lower Nubia. The assemblages included in this study cover about five millennia, spanning the period c. 8000 to c. 2500 BC.